Structures and properties of lead-free NKN piezoelectric ceramics - Jarupoom P. (2014)
In this work, the preparation of sodium potassium niobate (Na 0.5K0.5)NbO3 (NKN) ceramics were carried out by the conventional method. The effect of calcination temperatures, dwell time and heating rate on phase formation was investigated. Earlier work reported that to achieve the density of NKN ceramic over 95% of its theoretical density is rather difficult. In this work, firing conditions and heating and cooling rates were carefully varied to fabricate the NKN ceramics. X-ray diffraction (XRD) techniques were used to investigate the phase evolution of the calcined powders and sintered bodies. Microstructures of sintered pellets were studied by the scanning electron microscopic (SEM) techniques. Dielectric and ferroelectric properties were also investigated and reported.